REVIEW PENERAPAN SHADING DEVICE PADA DOUBLE SKIN FAÇADE UNTUK KENYAMANAN TERMAL DAN EFFISIENSI ENERGI BANGUNAN - Maria Lady Hendrik; Rahmayanti Rahmayanti (JAMBURA Journal of Architecture, 2023)
The application of Double Skin Façade on the building envelope as an effort to save energy and increase thermal comfort, has been carried out for several decades. The application of DSF design parameters needs to be considered to achieve maximum energy savings and thermal comfort. A shading device as one of the parameters in the DSF not only functions as a shade but can also reduce heat entering the room. This study focuses on the effectiveness of applying a shading device in the DSF cavity for thermal comfort and energy efficiency of buildings. The literature review method was used to review previous studies that had been carried out, by examining the shading parameters to see their effect on comfort and energy savings. The results show that the positioning of the shading device can reduce energy use and increase thermal comfort significantly.